2007
DOI: 10.1007/s11745-007-3043-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipophilic Antioxidant Efficacy in Vivo by the Biomarkers Hydroxyoctadecadienoic Acid and Isoprostane

Abstract: The evaluation of antioxidant activity in vivo is difficult. In this study, the effects of dietary natural and synthetic antioxidants on the lipid peroxidation in mice were assessed using a biomarker, total hydroxyoctadecadienoic acid (tHODE). Biological samples such as plasma, erythrocytes, and tissues were first reduced and then saponified to convert various oxidation products of linoleates to tHODE. Subsequently, the absolute concentration of tHODE and its stereoisomer ratio, [9- and 13-(Z,E)-HODE)/[9- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Furthermore, the stereoisomer ratio in plasma and liver exhibited a significant inverse correlation with age (data not shown), which has also been observed in a human plasma study [18]. Additionally, the plasma levels of tHODE were significantly correlated with liver and brain levels of tHODE (data not shown), consistent with our previous observations [19].…”
Section: Correlation Studysupporting
confidence: 89%
“…Furthermore, the stereoisomer ratio in plasma and liver exhibited a significant inverse correlation with age (data not shown), which has also been observed in a human plasma study [18]. Additionally, the plasma levels of tHODE were significantly correlated with liver and brain levels of tHODE (data not shown), consistent with our previous observations [19].…”
Section: Correlation Studysupporting
confidence: 89%
“…In this study, experimental animals were used as an antioxidant evaluation model. In such studies, a vitamin E-depleted diet accelerates lipid peroxidation in vivo, which was observed in this study and also in previously reported studies 6,11) . Thus, this model is suitable for the evaluation of antioxidant mixtures in vivo using biomarkers as measures of lipid peroxidation.…”
Section: 8 2asupporting
confidence: 90%
“…In a previous study using mice, we observed the significant influence of the lipophilic antioxidants on biomarkers in the blood and tissues compared with a vitamin E-depleted diet 11) . Accordingly, in the present study, we administered coffee and its components, chlorogenic acid, caffeic acid, and caffeine, as a drinking water to mice fed a vitamin E-depleted diet for a relatively long period (1 month).…”
Section: Resultsmentioning
confidence: 84%
“…Consequently, the formation of tocopheroxyl radical reacts with another peroxyl radical, thereby forming non radical products. In humans and experimental animals, vitamin E suppresses the production of isoprostanes, an index of lipid peroxidation (29, 30). By protecting against peroxidation, vitamin E becomes consumed rapidly and regenerated back to its reduced form by the cytoplasmic antioxidant cycling network that includes vitamin C and thiol antioxidants, such as glutathione and lipoic acid (31).…”
Section: Vitamin E Pharmacodynamicsmentioning
confidence: 99%